The school survival guide for kids with LD* : (*learning differences) - Cummings, Rhoda Woods; Fisher, Gary L.; Espeland, Pamela, 1951- (Minneapolis : Free Spirit Pub., 1991)
Discusses how children with "learning differences" can get along better in school.
Includes bibliographical references (p. 153-160) and index.
Keywords: Learning disabled children -- Education -- United States -- Handbooks, manuals, etc. -- Juvenile literature; Learning disabilities -- United States -- Handbooks, manuals, etc. -- Juvenile literature; Learning disabilities